2017
DOI: 10.1155/2017/2351037
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii Infection in Transfusion Dependent Thalassemia Patients with Sepsis

Abstract: Purpose To identify the Acinetobacter baumannii infection among transfusion dependent thalassemia patients. Methods A quantitative approach was employed to assess Acinetobacter baumannii infection in transfusion dependent thalassemia patients. Samples were collected from 916 patients, which have shown bacterial growth on MacConkey and blood agar culture media. A. baumannii strains were identified by microbiological methods and Gram's staining. API 20 E kit (Biomerieux, USA) was used for final identification. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…pneumoniae and L. monocytogenes [17,18]. Similar local and regional studies were in agreement with the present study results that refer to the predomenance of Gram negative species in Thalssemia patients, especially K. pneumoniae [19,8].…”
Section: (100%)supporting
confidence: 93%
See 1 more Smart Citation
“…pneumoniae and L. monocytogenes [17,18]. Similar local and regional studies were in agreement with the present study results that refer to the predomenance of Gram negative species in Thalssemia patients, especially K. pneumoniae [19,8].…”
Section: (100%)supporting
confidence: 93%
“…Microorganisms such Yersinia enterocolitica, Klebsiella spp., Escherichia coli, Streptococcus pneumonia, Pseudomonas aeruginosa and Listeria monocytogenes have been reported in the state of iron overload. A previous study revealed that splenectomy predisposed thalassemia and sickle cell disease patients to severe infections mostly by Gram-negative microorganisms [8]. Polymerase chain reaction (PCR) is considered the most well developed molecular technique for the detection of various diseases [9].…”
Section: Introductionmentioning
confidence: 99%
“…Acinetobacter baumannii is one of the most multidrug-resistant pathogens of the ESKAPE group ( Enterococcus faecium , Staphylococcus aureus , Klebsiella pneumoniae , Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter spp. ), which causes hospital-acquired infections leading to excessive inflammatory reactions, sepsis, septic shock and even death 5 . Recently, A. baumannii has become increasingly important because it has extensive drug resistance to all clinical antibiotics, and the A. baumannii infection mortality rate can reach 35%.…”
Section: Introductionmentioning
confidence: 99%
“…A. baumannii infections trigger excessive inflammatory reactions, leading to endotoxic shock, sepsis, and even death ( Routsi et al, 2010 ; Muzaheed et al, 2017 ). Sepsis, is a systemic inflammatory response syndrome (SIRS) caused by infections of pathogenic microorganisms, especially gram-negative bacteria ( Carcillo and Fields, 2002 ; Uhle et al, 2015 ; Sehgal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%